2021
DOI: 10.1155/2021/8684725
|View full text |Cite
|
Sign up to set email alerts
|

Acteoside Counteracts Interleukin‐1β‐Induced Catabolic Processes through the Modulation of Mitogen‐Activated Protein Kinases and the NFκB Cellular Signaling Pathway

Abstract: Osteoarthritis (OA) is the most common degenerative joint disease with chronic joint pain caused by progressive degeneration of articular cartilage at synovial joints. Acteoside, a caffeoylphenylethanoid glycoside, has various biological activities such as antimicrobial, anti-inflammatory, anticancer, antioxidative, cytoprotective, and neuroprotective effect. Further, oral administration of acteoside at high dosage does not cause genotoxicity. Therefore, the aim of present study is to verify the anticatabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For instance, it has been shown to attenuate the X-rayinduced intracellular ROS and apoptosis in human skin fibroblasts via mitogen-activated protein kinase (MAPK) signaling [34]. Another study demonstrated that verbascoside inhibited various inflammatory mediators in the primary rat chondrocytes treated with IL-1β through the MAPK pathway as well [35]. Moreover, recent studies have suggested verbascoside possessed the anti-diabetic potential since it has been reported to lower hyperglycemia and hyperlipidemia in diet/STZ-induced diabetic rats [36].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown to attenuate the X-rayinduced intracellular ROS and apoptosis in human skin fibroblasts via mitogen-activated protein kinase (MAPK) signaling [34]. Another study demonstrated that verbascoside inhibited various inflammatory mediators in the primary rat chondrocytes treated with IL-1β through the MAPK pathway as well [35]. Moreover, recent studies have suggested verbascoside possessed the anti-diabetic potential since it has been reported to lower hyperglycemia and hyperlipidemia in diet/STZ-induced diabetic rats [36].…”
Section: Discussionmentioning
confidence: 99%
“…In a 12 h light/dark cycle, free access to food and water were offered to all mice. APP/PS1 mice were stochastically assigned to two groups: (i) the model group that was orally treated with 0.4 mL of normal saline ( n = 12) daily for 6 weeks and (ii) the VB-treated group that was orally treated during the same period with 10 mg/kg of VB (61276-17-3, 98.38% purity, Chengdu Herbpurify Co., Ltd., Chengdu, China), which was firstly dissolved with DMSO (1/2000 V total ) before diluting with normal saline ( n = 12) [ 23 , 24 ]. WT mice ( n = 12) were administered 0.4 mL of normal saline daily for 6 weeks through the gastric route and served as the control group.…”
Section: Methodsmentioning
confidence: 99%
“… [121] Bone and cartilage protection Rats Inhibits MMP-13, MMP-3, and MMP-1 expression by decreasing MAPK/NF-κB signaling. [19] Mice Reduces osteoclastogenesis by attenuation of NF-κB pathway and stimulation of PI3K/AKT pathway. [125] MC3T3-E1 Enhances proliferation and differentiation by increasing IGF-1/BMP/PI3K/mTOR signaling [127] …”
Section: Pharmacokinetic Profilesmentioning
confidence: 99%
“…In addition, Srivastava also discusses some pharmacological activities of AC [12] . From the sophisticate literature research, we find that AC has been reported various pharmacological activities, including anti-oxidation [14] , anti-inflammation [15] , anti-cancer [11] , neuroprotection [16] , cardiovascular protection [17] , anti-diabetes [18] , bone and cartilage protection [19] , hepatoprotection [20] , and anti-microorganism [21] . In this review, we will mainly focus on these fields and summarize the research progress of AC, including the pharmacokinetic profiles.…”
Section: Introductionmentioning
confidence: 99%